2017
DOI: 10.1111/os.12356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intra‐wound Vancomycin for Spinal Surgery: A Systematic Review and Meta‐analysis

Abstract: Intra-site prophylactic vancomycin in spine surgery is an effective method of decreasing the incidence of postsurgical wound infection. However, there are differences in the prophylactic programs used for various spinal surgeries. Thus, this systematic review and meta-analysis aimed to evaluate the effectiveness of using intra-wound vancomycin during spinal surgery and to explore the effects of dose-dependence and the method of administration in a subgroup analysis. A total of 628 citations or studies were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 46 publications
1
18
1
Order By: Relevance
“…The effectiveness of vancomycin powder has been documented more extensively in other orthopedic subspecialties than foot and ankle. 1,3-5,10 A systematic literature review by Kanj et al 5 showed local vancomycin-impregnated cement and powder to be associated with lower infection rates while also being safe and effective in clean orthopedic surgery. The authors especially recommended using local vancomycin in spine surgery, in which patients without local antibiotic prophylaxis were more than 4 times more likely to experience a deep postoperative wound infection.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of vancomycin powder has been documented more extensively in other orthopedic subspecialties than foot and ankle. 1,3-5,10 A systematic literature review by Kanj et al 5 showed local vancomycin-impregnated cement and powder to be associated with lower infection rates while also being safe and effective in clean orthopedic surgery. The authors especially recommended using local vancomycin in spine surgery, in which patients without local antibiotic prophylaxis were more than 4 times more likely to experience a deep postoperative wound infection.…”
Section: Rationalementioning
confidence: 99%
“…Evaniew et al 4 concluded through their meta-analysis that there is a lack of high-quality evidence to inform the use of intrawound vancomycin in spine surgery. Xie et al 10 found from their meta- analysis on intrawound vancomycin in spinal surgery that the odds of developing postsurgical wound infection without prophylactic local vancomycin use were 2.83-fold higher than the odds of experiencing wound infection with the use of intrawound vancomycin. Furthermore, a retrospective review performed by Singh et al 8 that assessed the efficacy of intraoperative vancomycin powder administration on preventing deep SSI in high-energy lower extremity trauma (including tibial plateau fractures and pilon fractures) found that the rate of deep SSI between the groups was not significantly different.…”
Section: Rationalementioning
confidence: 99%
“…However, studies have shown that systemic vancomycin administration may not provide sufficient bone and tissue concentrations in some orthopaedic settings (Bue et al, 2015(Bue et al, , 2017Bryson et al, 2016;Mangram et al, 1999). Local vancomycin application has the potential to bypass these concerns by delivering high target-site concentrations without reaching toxic sideeffects (Sweet et al, 2018;Whiteside, 2016;Young et al, 2014;Wahl et al, 2017). Several local vancomycin applications and carriers are currently available, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…powder, calcium sulfate, and irrigation. Particularly in implant surgery, local vancomycin application may be promising to prevent bacterial implant colonization (Whiteside, 2016;Young et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation